Isolation and Functional Characterization of a Floral Repressor, BcMAF1, From Pak-choi (Brassica rapa ssp. Chinensis) - Huang, Feiyi; Liu, Tongkun; Hou, Xilin (Frontiers in Plant Science, 2018)
MADS-box genes form a large gene family in plants and are involved in multiple biological processes, such as flowering. However, the regulation mechanism of MADS-box genes in flowering remains unresolved, especially under short-term cold conditions. In the present study, we isolated BcMAF1, a Pak-choi (Brassica rapa ssp. Chinensis) MADS AFFECTING FLOWERING (MAF), as a floral repressor and functionally characterized BcMAF1 in Arabidopsis and Pak-choi. Subcellular localization and sequence analysis indicated that BcMAF1 was a nuclear protein and contained a conserved MADS-box domain. Expression analysis revealed that BcMAF1 had higher expression levels in leaves, stems, and petals, and could be induced by short-term cold conditions in Pak-choi. Overexpressing BcMAF1 in Arabidopsis showed that BcMAF1 had a negative function in regulating flowering, which was further confirmed by silencing endogenous BcMAF1 in Pak-choi. In addition, qPCR results showed that AtAP3 expression was reduced and AtMAF2 expression was induced in BcMAF1-overexpressing Arabidopsis. Meanwhile, BcAP3 transcript was up-regulated and BcMAF2 transcript was down-regulated in BcMAF1-silencing Pak-choi. Yeast one-hybrid and dual luciferase transient assays showed that BcMAF1 could bind to the promoters of BcAP3 and BcMAF2. These results indicated that BcAP3 and BcMAF2 might be the targets of BcMAF1. Taken together, our results suggested that BcMAF1 could negatively regulate flowering by directly activating BcMAF2 and repressing BcAP3.